SOCIO-PHILOSOPHICAL ANALYSIS OF PERSONAL PROBLEMS IN THE GLOBAL WORLD - Majitov Makhmud (Scholar Express Journal, 2024)
In the article is scientifically analyzed the social philosophical problems of person socializing in the processes of globalization. So this article analyzes the concept of personality, its social essence, the phenomenon of the person, the processes related to its content, structure and specifications of the formation
Keywords: personality; individ; human